NiTiCu Transverse to Axial Strain Ratio Analysis During Tension/Compression Tests. (2015) - Fabregat-Sanjuan, A.; Ferrando, F.; De la Flor, S.
Abstract: Tension-compression asymmetry in polycrystalline NiTiCu tubes was studied during elastic and transformation zone using strain gauges rosettes. Axial and transverse strain measurements from strain gauges were used to calculate a localized strain ratio through tensile and compression tests at different temperatures. The results show an asymmetric tension/compression behavior from stress-axial strain curves and from strain ratio-axial strain curves with a non constant strain ratio. Different temperatures tests also show similar values of strain ratio for martensite and austenite phases in the elastic zone.